The use of various composition media and additional compost to stimulate the growth of jabon putih (Neolamarckia cadamba (Roxb.) Bosser) seedlings - Suhartati; Meryana Kiding Allo (Foresty Faculty of Hasanuddin University, 2022)
Jabon putih (Neolamarckia cadamba (Roxb.) Bosser) is a species of forest plant that is widely grown for pulp raw material of paper and carpentry wood, in plantation forests, village forests, and community lands, so it is necessary to prepare good quality seedlings. This research was conducted for the propagation of jabon putih seedlings by stimulating their growth using various media compositions and compost doses. This research was carried out in the nursery area of the Environmental and Forestry Research and Development Center of Makassar for three months, from October 2019 to January 2020. This study used a completely randomized design with a factorial pattern with four replications. The treatment used various media compositions consisting of soil, sand, husks as the first factor, and compost dose as the second factor. The variables observed were the growth of seedlings including height, stem diameter, and number of leaves. The interaction of media composition and compost dose had a significant effect on the growth of jabon putih seedlings in the nursery. The best media composition was a mixture of soil, husks, and sand with a ratio of 2:1:1 and the provision of 40 g of compost per polybag, which could increase the growth of seedling height by 68.62%.